Health Sciences 2019
DOI: 10.35988/sm-hs.2019.106
|View full text |Cite
|
Sign up to set email alerts
|

Canine-Assisted Therapy and the Improvement of Physical Characteristics in Disabled Children: A Pilot Study

Abstract: Materials and methods. Three groups of mentally disabled children of different age participated in dog-assisted therapy sessions twice per week for two months. Motor skills evaluation was based on the Bruininks-Oseretsky motor skills evaluation test (short version). Isometric torso muscle endurance tests were based on Ito, McIntosh and McGill. The ability to focus and memorise exercises and the ability to understand and perform them was also evaluated. Results. Movement perception and performance, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Em relação à motivação para habilidades motoras, as mudanças observadas antes e após as sessões de terapia com a utilização de cães terapeutas foram semelhantes às de estudos anteriores 10,14,15 . Como complemento, Nedzinskaitė et al 13 relataram que, além de atuarem como motivadores de performance, os cães auxiliam em diversas tarefas, reduzindo tensão e ansiedade, como notado nas atividades de G1C e G2C.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Em relação à motivação para habilidades motoras, as mudanças observadas antes e após as sessões de terapia com a utilização de cães terapeutas foram semelhantes às de estudos anteriores 10,14,15 . Como complemento, Nedzinskaitė et al 13 relataram que, além de atuarem como motivadores de performance, os cães auxiliam em diversas tarefas, reduzindo tensão e ansiedade, como notado nas atividades de G1C e G2C.…”
Section: Discussionunclassified
“…Em outro estudo, destaca-se a reabilitação positiva dos pacientes que realizaram a terapia com os animais, a abordagem proativa dos cães e a reciprocidade entre terapeutas e pacientes 13 . Ademais, Nobre et al 27 e Lundqvist et al 7 demonstraram os benefícios que a TAA propicia aos pacientes, evidenciando sua contribuição para a socialização, afetividade, relaxamento, descontração, motricidade global, atenção, foco e interesse pelo ambiente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…During physical therapy, children with special needs working with therapy dogs demonstrated increased movement perception and performance. Students with physical disabilities also exhibited improved memory function and ability to focus, showing a significant enhancement in motor skills and coordination (Nedzinskaitė et al, 2019). Finally, one study also showed that AAI increases the level of oxytocin, the hormone of attachment, in the blood (Beetz et al, 2012).…”
Section: Physiological Effectsmentioning
confidence: 95%
“…One of the ways this interaction can be used is by animal-assisted therapy (AAT), which consists in the use of animals for therapeutic purposes 9 . The use of dogs in therapies with children has contributed to increase self-esteem, improve motor skills, social interaction and behavioral reactions, promote relaxation and joy, and offer security [10][11][12][13] . The presence of a therapy dog allows for infants to remain more focused and aware of their social environment 14,15 .…”
Section: Introductionmentioning
confidence: 99%